STRATEGI SMART BRANDING DALAM PEMBANGUNAN SMART CITY DI KABUPATEN DEMAK - EB, Gita Aprinta; Pungkasanti, Prind Triajeng; Handayani, Titis (Interaksi: Jurnal Ilmu Komunikasi, 2024)
The integration of smart city concepts into urban management has become a prominent strategy for addressing global urbanization challenges. This study examines the implementation of smart branding strategies within the smart city framework of Demak Regency, Indonesia. Drawing from qualitative methods, including interviews with local authorities and focus group discussions with community stakeholders (14 people),, the research highlights the alignment of smart branding initiatives with sustainable development goals and the enhancement of local economic potential. Smart branding in Demak emphasizes leveraging cultural and historical identity, transitioning from its traditional image as a "Wali City" to a dynamic "City of Street Cultural Events." Key initiatives include the Tembiring Creative Fun program, the SIPARTALI tourism system, and the utilization of social media platforms like "Dolan Demak" to promote tourism and community engagement. The results underline the importance of collaboration among government sectors, private stakeholders, and local communities to optimize the branding strategy. Despite achieving initial milestones, challenges persist, such as insufficient community participation and limited inter-departmental collaboration. The study concludes by advocating for a more inclusive, collaborative approach to ensure the sustainability and effectiveness of smart branding in fostering economic development and cultural preservation in Demak Regency.